KEPIMPINAN KEPALA DESA DALAM MENINGKATKAN PARTISIPASI MASYARAKAT TERHADAP PELAKSANAAN PEMBANGUNAN DESA - DEDI SUPRIADI (GANEC SWARA, 2021)
The village head is the head of government at the village level is expected to be able to run the village government well in providing services to the community, so that if the village head shows good performance in the administration of village governance, it will also affect the performance of government at the district, provincial and central levels . The village head as a leader in the village scope has aspects of a distinctive personality / leadership style that can support his efforts in realizing good relations with members of his community. The style of leadership of the village head is closely related to the objectives to be achieved by a village government. Therefore, the leadership style of the village head is always associated with the activities of the village head in directing, motivating, communicating, decision making, and supervising members to realize the objectives of village governance. The purpose of this study was to determine the leadership style of the village head in the physical development of the village.     The results showed that the Village Head Leadership Style in Increasing Community Participation in the Physical Development of Uma Beringin Village, Unter Iwes District, Sumbawa Regency in general, according to researchers, is good, and the village head can be said to be a democratic leadership style, because it is always open to subordinates and conducts joint deliberations. BPD and other village officials and the community